Becoming Native-Like for Good or Ill: Online and Offline Processing of Case Forms in L2 Russian - Cherepovskaia, Natalia; Reutova, Elizaveta; Slioussar, Natalia (Frontiers in Psychology, 2021)
One of the central questions in second language processing studies is whether native (L1) and second language (L2) readers process sentences relying on the same mechanisms or there are qualitative differences. As their proficiency grows, L2 readers become more efficient, but it is difficult to determine whether they develop native-like mechanisms or rely on different strategies. Our study contributes to this debate by focusing on constructions that were demonstrated to cause characteristic problems in L1 processing: a particular type of case errors in Russian was taken as an example. We investigated how beginner and intermediate learners of Russian process such errors, measuring reading times and grammaticality judgment accuracy. At the beginner level, we found non-native-like patterns both in online and in offline measures. But at the intermediate level, native-like problems emerged in offline measures. In our view, this is a strong indication that these readers are using the same underlying mechanisms as in L1 processing. In online measures, L2 readers at both levels were, in general, much slower than native participants and exhibited characteristic non-native-like patterns, which we explained by delayed morphosyntactic processing. We conclude that our results are compatible with approaches, assuming that the mechanisms for L1 and advanced L2 processing are the same, but L2 processing is more cognitively demanding and therefore slower.